Teachers' Bias Against the Mathematical Ability of Female, Black, and Hispanic Students. (January 2020) - Copur-Gencturk, Yasemin; Cimpian, Joseph R.; Lubienski, Sarah Theule; Thacker, Ian
Researchers have long endeavored to understand whether teachers' evaluations of their students' mathematical ability or performance are accurate or whether their evaluations reveal implicit biases. To disentangle these factors, in a randomized controlled study (N = 390), we examined teachers' evaluations of 18 mathematical solutions to which gender- and race-specific names had been randomly assigned. Teachers displayed no detectable bias when assessing the correctness of students' solutions; however, when assessing students' mathematical ability, biases against Black, Hispanic, and female students were revealed, with biases largest against Black and Hispanic girls. Specifically, non-White teachers' estimations of students' mathematical ability favored White students (both boys and girls) over students of color, whereas (primarily female) White teachers' estimations of students' mathematical ability favored boys over girls. Results indicate that teachers are not free of bias, and that teachers from marginalized groups may be susceptible to bias that favors stereotype-advantaged groups.